Behavioral studies of Black-capped Chickadees at the UWM Field Station - (:unkn) unknown (My University, 1982)
This report summarizes studies of the behavior of Black-capped Chickadees (Parus atricapillus) conducted at the UWM Field Station since 1970. Vocalizations and responses to predators are emphasized. Chickadees are very social and their calls are more complex than those of non-social avian species.
Keywords: Black-capped Chickadee; behavior; Parus atricapillus; vocalizations